EFEKTIFITAS KOMPOS TANAMAN Crotalaria juncea PADA KETERSEDIAAN DAN SERAPAN N, P, K SERTA PERTUMBUHAN TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) PADA ENTISOL WAJAK, MALANG - Laksono Raditya; Retno Suntari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
The problem of Entisol used for agricultural land is the loss of nutrients due to leaching and evaporation. It is thus necessary to keep the nutrients available in the soil. The purpose from this research was (1) to know the effectiveness of Crotalaria juncea compost application on the availability of N, P, and K on Entisol Wajak, and (2) to assess the effectiveness of Crotalaria juncea compost application on uptake of N, P, K and growth of sweet corn in an Entisol of Wajak, Malang. This research used a completely randomized design with five treatments and three replications, i.e. C0 (Urea 100%), C1 (Crotalaria juncea compost 100% + Urea 75%), C2 (Crotalaria juncea compost 100% + Urea 75%), C3 (Crotalaria juncea compost 100%), C4 (Crotalaria juncea compost 200%). The results showed that application of Crotalaria juncea compost 100% (10 t ha-1) did not significantly affect available-P but it significantly increased available-N at 4 and 8 weeks with the effectiveness of 39% and 79.66%, and significantly increased the available-K at 8 and 12 weeks with effectiveness of 38.75% and 33.33% compared to 100% urea application (288 kg ha-1). Applications of 100% Crotalaria juncea compost (10 t ha-1) did not significantly affect plant growth (dry weight and plant height) as well as the N and K uptake, but increased the effectiveness of the P uptake 2.07% compared to 100% urea application (288 kg ha-1).